INAP: An integrated network analysis pipeline for microbiome studies. Issue 2 (16th March 2022) - Feng, Kai; Peng, Xi; Zhang, Zheng; Gu, Songsong; He, Qing; Shen, Wenli; Wang, Zhujun; Wang, Danrui; Hu, Qiulong; Li, Yan; Wang, Shang; Deng, Ye
Abstract: Integrated network analysis pipeline (iNAP) is an online analysis pipeline for generating and analyzing comprehensive ecological networks in microbiome studies. It is implemented in two sections, that is, network construction and network analysis, and integrates many open‐access tools. Network construction contains multiple feasible alternatives, including correlation‐based approaches (Pearson's correlation and Spearman's rank correlation along with random matrix theory, and sparse correlations for compositional data) and conditional dependence‐based methods (extended local similarity analysis and sparse inverse covariance estimation for ecological association inference), while network analysis provides topological structures at different levels and the potential effects of environmental factors on network structures. Considering the full workflow, from microbiome data set to network result, iNAP contains the molecular ecological network analysis pipeline and interdomain ecological network analysis pipeline (IDENAP), which correspond to the intradomain and interdomain associations of microbial species at multiple taxonomic levels. Here, we describe the detailed workflow by taking IDENAP as an example and show the comprehensive steps to assist researchers to conduct the relevant analyses using their own data sets. Afterwards, some auxiliary tools facilitating the pipeline are introduced to effectively aid in the switch from local analysis to online operations. Therefore, iNAP, as an easy‐to‐use platform that provides multiple network‐associated tools and approaches, can enable researchers to better understand the organization of microbial communities. iNAP is available at http://mem.rcees.ac.cn:8081 with free registration. Abstract : Integrated network analysis pipeline (iNAP) contains two network analyses pipelines for intradomain and interdomain associations of microbial species at multiple taxonomic levels, that is, molecular ecological network analysis pipeline and interdomain ecological network analysis pipeline. iNAP provides multiple approaches and methods for network analysis of microbiome studies, including SparCC, eLSA, SPIEC‐EASI, and RMT‐based Pearson's or Spearman's correlations. Through free registration and easy operations, iNAP can be easily operated by researchers without any prerequisite bioinformatics or statistical language‐based programming skills for network analyses of microbiome studies. Highlights: Integrated network analysis pipeline (iNAP) contains two network analyses pipelines for intradomain and interdomain associations of microbial species at multiple taxonomic levels, that is, molecular ecological network analysis pipeline and interdomain ecological network analysis pipeline. iNAP provides multiple approaches and methods for network analysis of microbiome studies, including SparCC, eLSA, SPIEC‐EASI, and RMT‐based Pearson's or Spearman's correlations. Through free registration and easy operations, iNAP can be easily operated by researchers without any prerequisite bioinformatics or statistical language‐based programming skills for network analyses of microbiome studies.